If x + x 1 = 5 , then find the value of ( x − 2 ) 2 + ( x − 2 ) 2 2 5 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given that x + x 1 = 5 ⟹ x 2 − 5 x + 1 = 0 . Then
( x − 2 ) 2 + ( x − 2 ) 2 2 5 = x 2 − 4 x + 4 + x 2 − 4 x + 4 2 5 = x 2 − 5 x + 1 + x + 3 + x 2 − 5 x + 1 + x + 3 2 5 = x + 3 + x + 3 2 5 = x + 3 ( x + 3 ) 2 + 2 5 = x + 3 x 2 + 6 x + 9 + 2 5 = x + 3 x 2 − 5 x + 1 + 1 1 x + 8 + 2 5 = x + 3 1 1 x + 3 3 = 1 1 Note that x 2 − 5 x + 1 = 0
x + x 1 = 5 ⇔ x 2 − 5 x + 1 = 0 ⇔ ( x − 2 ) 2 − x − 3 = 0 ⇔ ( x − 2 ) 2 = x + 3
Let ( x − 2 ) 2 + ( x − 2 ) 2 2 5 = k , then
x + 3 + x + 3 2 5 = k ⇔ ( x + 3 ) 2 − k ( x + 3 ) 2 + 2 5 = 0 ⇔ x 2 + x ( 6 − k ) + ( 3 4 − 3 k ) = 0
We also know from earlier that x 2 − 5 x + 1 = 0 . By comparing coefficients, − 5 = 6 − k and 1 = 3 4 − 3 k must both be satisfied. Both of these equations produce k = 1 1 .
Problem Loading...
Note Loading...
Set Loading...
Given x + x 1 = 5 , x is a solution to x 2 − 5 x + 1 = 0 . ( 1 )
Thus x 2 − 4 x + 4 = x + 3 , i.e. ( x − 2 ) 2 = ( x + 3 ) . ( 2 )
We can use Equation ( 2 ) to substitute in the expression:
( x − 2 ) 2 + ( x − 2 ) 2 2 5 = ( x + 3 ) + x + 3 2 5 .
Let t be the value of this expression: t = ( x + 3 ) + x + 3 2 5 .
Then t ( x + 3 ) = ( x + 3 ) 2 + 2 5 = x 2 + 6 x + 3 4 . ( 3 )
Use Equation ( 1 ) to get the identity x 2 = 5 x − 1 . ( 4 ) Use ( 4 ) to substitute for x 2 in ( 3 ) .
Then t ( x + 3 ) = 5 x − 1 + 6 x + 3 4 = 1 1 x + 3 3 = 1 1 ( x + 3 ) . The solution is t = 1 1 .